2012
DOI: 10.1159/000335282
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Vitamin D Status among Overweight and Obese Puerto Rican Adults

Abstract: Background/Aims: Low vitamin D status is highly prevalent worldwide, and the major determinants are sun exposure and vitamin D intake. We aimed to measure vitamin D status in a sample of overweight/obese adults in Puerto Rico, an area with plenty of sun exposure, and relate it to vitamin D intake, sun exposure and body composition. Methods: Serum 25(OH)D levels (liquid chromatography-tandem mass spectrometry), body weight and fat (bioimpedance), vitamin D intake and sun exposure (questionnaires) were assessed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 100 publications
5
16
2
Order By: Relevance
“…These findings are similar to those of a recent study of a convenience sample of 98 obese and overweight Puerto Rican adults without asthma, of whom 45% had vitamin D levels less than 30 ng/ml (28). The estimated prevalence of vitamin D insufficiency in children with asthma in Puerto Rico (a Caribbean island) is thus markedly higher than that reported for children with asthma living in Costa Rica (a Central American nation, 28%), and underscores the potential significance of vitamin D insufficiency on asthma morbidity in residents of areas with year-round sun exposure or near the Equator.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are similar to those of a recent study of a convenience sample of 98 obese and overweight Puerto Rican adults without asthma, of whom 45% had vitamin D levels less than 30 ng/ml (28). The estimated prevalence of vitamin D insufficiency in children with asthma in Puerto Rico (a Caribbean island) is thus markedly higher than that reported for children with asthma living in Costa Rica (a Central American nation, 28%), and underscores the potential significance of vitamin D insufficiency on asthma morbidity in residents of areas with year-round sun exposure or near the Equator.…”
Section: Discussionsupporting
confidence: 89%
“…The present study showed that higher BMI is associated with lower basal 25OHD in the sample as a whole. This is consistent with the reported in the literature negative association between 25OHD levels and obesity [59][60][61][62][63][64][65][66]. This effect was not evident for each gender group; this may be due to a small sample size in each group.…”
Section: Vitamin D Deficiency and Night Shift Work O R I G I N A L P supporting
confidence: 92%
“…Although the island of Puerto Rico (PR) is located in a tropical region, to our knowledge there are only two recently published studies addressing vitamin D levels in Puerto Ricans. 29–30 The first 29 was a cross-sectional study consisting of 1,292 Puerto Rican adults (379 men and 913 women, ranging in age from 45 to 75 years) and showed geometric means for plasma 25(OH)D concentrations of 15.8±1.5 ng/ml for men and 16.0±1.5 ng/ml for women. According to these results, 68.6% of the participating men and 65.5% of the participating women were deficient (cutoff of <20 ng/ml).…”
mentioning
confidence: 99%